Présentation - Frédérique Langue (Mélanges de la Casa de Velázquez, 2017)
Stepping beyond the multiplicity of discourses regarding digital humanities, this dossier examines an experience which predates this but has not heretofore received due recognition, namely that involving Latin America, from the colonial to the contemporary era, including the present day, and the sources and challenges of the development of a record and of the writing of its on-line history. It likewise includes, in addition to a current balance for SHS researchers, cross-disciplinary discussions on the new conditions of production and dissemination of knowledge, particularly in the sphere of history and epistemological practices. Also addressed is the question of digital governance and the relationships between research and free access, that is of scientific communication as conceived by its practitioners—the various constituencies who come under the heading of «digital humanists», both researchers and custodians of the digital heritage.